TOXICITY TEST OF BAY LEAF EXTRACT ON BHK-21 FIBROBLAST CELLS IN VITRO - Chintya Dewi Styo Ningrum; Debby Saputera; Rahmad Arifin (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Denture stomatitis is an inflammatory reaction in the oral mucosa that support the denture. This lesion is caused by the fungus Candida albicans and can be avoided by always maintain the cleanliness of denture. Bay leaf (Syzygium polyanthum) has flavonoid as the highest content which has antifungal and antioxidant properties so that bay leaf can be used as alternative ingredient for denture cleanser. Toxicity test needs to be done to determine the safety of this material. Objective: to analyze the toxicity of bay leaf extract (Syzygium polyanthum) to BHK-21 fibroblast cells using the MTT assay method. Method: This study is a true experimental study, which using posttest-only with control group design. The group, treated with bay leaf extract, were 25%, 20%, 15%, 10% and 5% concentrations including 2 control groups which were media control and cell control. Absorbance was read using ELISA reader and cell viability was calculated. Results: The percentage of living cells in all groups which treated with bay leaf extract was 100%. The parametric analysis of One Way Annova showed that there was no significant difference. Conclusion: Bay leaf extract (Syzygium polyanthum) does not have any toxic effect to BHK-21 fibroblast cell using the MTT assay method because cell viability in all treatment groups was ≥ 60%.